Shame and Burden: Family Stigma in Caring for Shackled Individuals with Mental Disorders - Holis, Willi; Rohman, Atiqur; Yaya, Mery Eka (Inspirasi Foundation, 2024)
Introduction: Mental disorders remain a significant public health concern, often leading to stigma and social discrimination, particularly for families caring for affected individuals. In some cases, shackling (physical restraint) is still practiced due to limited access to mental health services, further intensifying the burden on caregivers. Objective: This study aims to explore the family experiences of stigma and emotional burden in providing care for shackled individuals with mental disorders. Method: A qualitative research design with a phenomenological approach was employed. The study was conducted within the scope of the Pamekasan District Health Office, involving families of mentally ill patients as participants. Inclusion criteria included participants who had cared for restrained family members for over a year, were above 20 years old, willing to participate, and able to communicate verbally. A snowball sampling technique was used, where key informants assisted in identifying additional participants. Results: Participants reported experiencing stigma related to their role in caring for family members with mental disorders who had been restrained. The findings highlight psychological and emotional reactions, as well as how participants navigate daily life amid societal stigma. A key subtheme,